Study on fabrication and mechanical properties of Al-SiC nano-composite materials - Lim, Mei Jing (2016)
The development of metal matrix composite (MMC) has set the stage for a new revolution in materials. Aluminium Silicon Carbide (Al-SiC) nano-MMC has better mechanical properties than micro-MMC and has extremely high strength and hardness. The Al-SiC nano-composites were fabricated using powder metallurgy method to produce a more uniform distributed structure. Compactions of the nano-composites were performed using hydraulic press and a cylindrical shaped die. Two compaction loads, 15 Ton and 20 Ton, have been used to fabricate the nano-composite. The Al-SiC nano-composites have been sintered in two different temperatures. Green uniaxial press compacts in the different compaction load of 15 Ton and 20 Ton were sintered at the temperatures of 580°C and 600°C. The heating rate of the sintering process was 5°C/min and the sintering time varied between at 4 hour and 5 hour. Hardness and density of the nano-composites were investigated. Besides that, the microstructure of sintered nano-composites has been examined and characterized. It was found that the compaction load and sintering temperatures have significantly affected the mechanical properties and microstructure of the nano-composites. Green and theoretical density increased with the increment of compaction pressure. Besides that, the nano-composites have a better hardness value with higher compaction load and higher sintering temperature. It is found in the research that the nano-composite with 20 Ton compaction load and 600°C sintering temperature provided better hardness value and microstructure as compared to the samples fabricated by other compaction load and sintering temperature. However, residual porosities were present in all sintered nano-composites under each sintering condition. This research demonstrated that the higher compaction load and sintering temperature contributed better mechanical properties for the nanocomposite.